2021
DOI: 10.3889/oamjms.2021.5808
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Integrated Management of Children Illness in Primary Health Community in Yogyakarta, Indonesia

Abstract: BACKGROUND: The mortality rate for infants and toddlers aged 12–59 months in Yogyakarta has shown a fluctuating trend between 2008 and 2014. To reduce infant and toddler mortality rates, the Yogyakarta city government has made some efforts to implement integrated management of children illness (IMCI). Thus, it can be said that one of the successful actions of the government in reducing mortality and morbidity of infants and toddlers is determined by optimizing the role of IMCI in the primary health community (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…More than half (6 out 8) of the articles analyzed indicated that the implementation of IMCI was not following the standards or procedures/steps in the IMCI guidelines or chart (Casnuri & Rahayu, 2020;Hasibuan et al, 2019;Mansur, 2017;Rahmah & Astuti, 2021;Suparmi et al, 2018;Wartana & Herawaty, 2016). This is closely related to a large number of untrained health workers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…More than half (6 out 8) of the articles analyzed indicated that the implementation of IMCI was not following the standards or procedures/steps in the IMCI guidelines or chart (Casnuri & Rahayu, 2020;Hasibuan et al, 2019;Mansur, 2017;Rahmah & Astuti, 2021;Suparmi et al, 2018;Wartana & Herawaty, 2016). This is closely related to a large number of untrained health workers.…”
Section: Methodsmentioning
confidence: 99%
“…Of the eight articles analyzed, six articles describe the condition shortage of IMCI officers due to the gap between officers and patients, and there are still officers who have never received IMCI training (Casnuri & Rahayu, 2020;Hasibuan et al, 2019;Mansur, 2017;Mastuti et al, 2021;Rahmah & Astuti, 2021;Wartana & Herawaty, 2016). One of the reasons for the absence of trained IMCI officers at the puskesmas is that the trained officers have moved and are no longer on duty at the puskesmas (Hasibuan et al, 2019).…”
Section: Manmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the implementation of the strategy is affected by the lack of human resources. A study by Rahmah and Astuti (2021) found shortage of IMCI-trained healthcare workers compared to the number of under-five children seen in the PHC facilities. The shortage increased the waiting times in the facilities.…”
Section: Barriers To the Involvement Of Guardians In Imcimentioning
confidence: 99%